2017
DOI: 10.3892/or.2017.5489
|View full text |Cite
|
Sign up to set email alerts
|

Berberine inhibits the proliferation of human nasopharyngeal carcinoma cells via an Epstein-Barr virus nuclear antigen 1-dependent mechanism

Abstract: Nasopharyngeal carcinoma (NPC) is a malignancy derived from the epithelial cells of the nasopharynx cavity, and is closely associated with Epstein-Barr virus (EBV) infection. In addition to NPC, EBV causes various human malignancies, such as gastric cancer, hematological tumors and lymphoepithelioma-like carcinomas. Epstein-Barr nuclear antigen 1 (EBNA1) encoded by EBV is indispensable for replication, partition, transcription and maintenance of viral genomes. Berberine, a naturally occurring isoquinoline alka… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 56 publications
0
25
0
Order By: Relevance
“…The plasmids pSG5 vector, pSG5-EBNA1, and pSG5-EBNA1ΔGA have been described previously 57 . The plasmid pEF-Flag-Hsp70 was constructed by inserting the Hsp70 sequence into the pEF vectors.…”
Section: Methodsmentioning
confidence: 99%
“…The plasmids pSG5 vector, pSG5-EBNA1, and pSG5-EBNA1ΔGA have been described previously 57 . The plasmid pEF-Flag-Hsp70 was constructed by inserting the Hsp70 sequence into the pEF vectors.…”
Section: Methodsmentioning
confidence: 99%
“…As natural medicines, traditional Chinese medicines have the advantages of a high level of safety, specific curative effect, and ability to avoid developing drug resistant disease. Researchers have been studying the efficacy and mechanism of traditional Chinese medicines, such as berberine [15], baicalein [16,17], arctiin [18], nitidine chloride [19], and other monomers [20] and have found them to exert obvious anticancer effects. However, significant future research will be needed on related fields in order to better develop the use of traditional Chinese medicines.…”
Section: Discussionmentioning
confidence: 99%
“…As speculated, V-val EBNA1 had the anti-apoptosis effect similar to P-ala EBNA1. Our previous studies have reported that EBNA1 could assist malignance cells to inhibit berberine [ 34 ] or 17-DMAG [ 33 ]-induced cancer cells death. Here, both P-ala and V-val EBNA1 attenuated the killing effects of triptolide on EBV-positive and EBV-negative NPC cell lines, suggesting that targeting on EBNA1 is a substantial strategy of treating EBV-positive NPC.…”
Section: Discussionmentioning
confidence: 99%